Moderately halophilic bacterias producing hydrolytic biotechnological enzymes - Flores, Mónica L. (2010)
The aim of this study was to characterize moderately halophilic bacteria producing hydrolases of biotechnological interest. For that, 32 aerobic bacterial isolates were selected from salt environments such as Pilluana, Huacho, Maras, Chilca, Paracas and Ventanilla. The morphological and physiological properties and hydrolytic capacity to various substrates were determined for all isolates. Genotypic characterization was performed by amplification of bacterial 16S ribosomal gene and cutting with the Hae III enzyme. The isolates 23, 2, 24, 19, 2 and 6 showed hydrolytic activity for Tween 80, olive oil, starch, casein, lactose and DNA, respectively. Isolates L3CH and L2PAR hydrolyzed the most substrates, except for lactose and DNA, in contrast isolates P2RI-17 and M17 which only hydrolyze Tween 80. Twelve genetic profiles were obtained from the restriction analysis of amplified 16S ribosomal DNA restriction analysis, indicating that there are at least 12 bacterial species with high biotechnological potential for hydrolytic enzyme production.